Communicator Credibility in Validating Information: Hadith Perspective - Mukhlis Aliyudin; Ridwan Rustandi (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This study aims to explore aspects of communicator credibility from a hadith perspective. This study used a qualitative approach through content analysis. The researchers conducted data collection by exploring the literature on hadith criticism methods. A literature study was also carried out by tracing traditions related to the communicator's credibility. These traditions are mainly related to the character or personality contained in the personality of the Prophet Muhammad, including the characters of shiddîq, amanah, fathonah, and tablîgh. This study concludes that one of the crucial aspects in verifying and validating information is the communicator's credibility. In the era of information openness and accelerating digitalization of culture, verifying and validating the truth of information are biased. Thus, many social phenomena lead to disharmony and social disintegration amid the flow of information exchange. Hadith studies and the science of hadith reinforce the importance of communicator credibility as an effort to validate the information. Therefore, the audience or community possesses an authoritative source they can utilize as a reference for filtering and receiving information. Hadith and hadith science perspective assert that the building blocks of communicator credibility rely on intellectual, moral, and expertise aspects